Protokritik Leopold Kordeš med zametkom in nezmožnostjo - Jesenko, Primož (Amfiteater (Ljubljana), 2024)
The paper delves into the activity of Leopold Kordeš (1808–1879) in the years before the March Revolution in the Habsburg Empire and until 1850. It does so through the prism of the newspaper Carniolia (1838–1844), which, in the German language, was the first to materialise the (proto)critical treatment of theatre activity in Ljubljana. By following Kordeš in his roles as writer, editor and organiser, the article emphasises his pioneering initiative to establish a permanent Slovenian theatre in 1848 and closely examines his interference with the authority of Janez Bleiweis and the reasons why Kordeš, as the creator of the first germ of a platform for critical writing about theatre in Ljubljana (and in Slovenia), got caught in the flow of not remembering and eluded the canonical reception of personalities in Slovenian history.
Keywords: cancel cultureCarniolia; Carniolia; contours of a shared narrative; dinamika nacionalnih razmerij; dynamics of national relations; entering of Slovenian expression onto the stage; gledališko poorčilo; Illyrischen Blatt; Illyrisches Blatt; initiative for a permanent Slovenian stage 1848-1850; Janez Bleiweis; jezik kot nacionalni atribut; jezikovna izbira; kulturna kritika kulture skupne naracije; language as a national attributte; Leopold Kordeš; linguistic choice; national political gools; pobuda za stalno slovensko gledališče 1848-1850; prodiranje slovenskega izraza na oder; protocriticism; retreat; theatre report; umik